Carbon emission from deforestation, forest degradation and wood harvest in the temperate region of Hindukush Himalaya, Pakistan between 1994 and 2016. (November 2018) - Ahmad, Adnan; Liu, QI-Jing; Nizami, S.M.; Mannan, Abdul; Saeed, Sajjad
Abstract: Regional carbon emission related to deforestation, forest degradation, and wood harvest is critical in the development of national action plans and strategies for forest carbon management. In this study, using remote sensed and ground inventory data, deforestation, forest degradation, wood harvest and their integrated carbon losses between 1994 and 2016 in the temperate region of Pakistan were estimated. The present study revealed that deforestation was responsible for a net loss of 629 ha forest (29 ha yr −1 ), and 4948 ha (245 ha yr −1 ) forest was degraded. The total harvested wood was 681 km 3 (31 km 3 yr −1 ). Deforestation was responsible for the loss of 206 kMg C (9 kMg C yr −1 ), while emissions related to degradation and wood harvest account for 1757 kMg C (80 kMg C yr −1 ) and 221 kMg C (10 kMg C yr −1 ), respectively. These findings suggest that an increase in population with the partial protection of forests by policy, weak law enforcement, and cultural attitudes of the local people towards forests were the major drivers of deforestation and degradation between 1994 and 2016, as well as their integrated carbon emissions.